High-precision mass measurement of doubly magic 208Pb - Kromer, Kathrin; Lyu, Chunhai; Door, Menno; Filianin, Pavel; Harman, Zoltán; Herkenhoff, Jost; Huang, Wenjia; Keitel, Christoph H.; Lange, Daniel; Novikov, Yuri N.; Schweiger, Christoph; Eliseev, Sergey; et al. (The European physical journal. A, Hadrons and nuclei, 2022)
The absolute atomic mass of 208Pb has been determined with a fractional uncertainty of 7×10−11 by measuring the cyclotron-frequency ratio R of 208Pb41+ to 132Xe26+ with the high-precision Penning-trap mass spectrometer Pentatrap and computing the binding energies EPb and EXe of the missing 41 and 26 atomic electrons, respectively, with the ab initio fully relativistic multi-configuration Dirac–Hartree–Fock (MCDHF) method. R has been measured with a relative precision of 9×10−12. EPb and EXe have been computed with an uncertainty of 9.1 eV and 2.1 eV, respectively, yielding 207.976650571(14) u (u=9.3149410242(28)×108 eV/c2) for the 208Pb neutral atomic mass. This result agrees within 1.2σ with that from the Atomic-Mass Evaluation (AME) 2020, while improving the precision by almost two orders of magnitude. The new mass value directly improves the mass precision of 14 nuclides in the region of Z = 81–84 and is the most precise mass value with A>200. Thus, the measurement establishes a new region of reference mass values which can be used e.g. for precision mass determination of transuranium nuclides, including the superheavies.
Gesehen am 18.01.2023
Im Titel ist die Zahl 208 hochgestellt